2010
DOI: 10.1002/anie.201002301
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Stability of Perovskite Oxides

Abstract: Perovskite oxides with general formula AMO 3 have a large variety of applications as dielectrics and piezoelectrics, [1] ferroelectrics [2] and/or ferromagnetic materials, [3] among others. Rare earth and alkaline earth metal perovskites are useful as catalysts for hydrogen generation, [4] as oxidation catalysts for hydrocarbons, [5] and as effective and inexpensive electrocatalysts for state-of-the-art fuel cells, [6] mainly due to the possibility of tuning their mixed ionic-electronic conductivity through s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
97
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 26 publications
7
97
1
1
Order By: Relevance
“…While comparisons between experimental and computed energies of reactions for solids exist in the literature, they tend to focus on very specific chemistries and/or crystal structures (e.g., perovskites 28,29 ). In contrast to the evaluation of molecular systems in the quantum chemistry field, 30,31 there is a lack of statistically broad studies on the accuracy of specific DFT functionals in predicting energies of reactions between solid phases.…”
Section: Introductionmentioning
confidence: 99%
“…While comparisons between experimental and computed energies of reactions for solids exist in the literature, they tend to focus on very specific chemistries and/or crystal structures (e.g., perovskites 28,29 ). In contrast to the evaluation of molecular systems in the quantum chemistry field, 30,31 there is a lack of statistically broad studies on the accuracy of specific DFT functionals in predicting energies of reactions between solid phases.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we expect higher uncertainty of first principle calculations compared to experiments. Nonetheless, deviation of assessed thermodynamic data from first principles results [23] was minimal. For Sr 3 Co 2 O 7 , A 0 and B 0 in Eq.5 were adjusted such as to make the phase stable at 1373 K in air in accordance with the findings from Aksenova et al and Cherepanov et al [34,65].…”
Section: Liquidmentioning
confidence: 84%
“…From the neutron diffraction experiments, the structure of two intermediate phases, SrCoO 2.75 and SrCoO 2.82±0.07 , were characterized. Calle-Vallejo et al [23] reported the Gibbs energy of formation for SrCoO 3 as −163 kJ/mol at 298 K obtained from first-principle calculations.…”
Section: Srcoo 3-δmentioning
confidence: 99%
See 2 more Smart Citations